Sb doping effects and oxygen adsorption in SnO2 thin films deposited via sol-gel - Geraldo,Viviany (2003)
Transparent electrically conducting antimony-doped SnO2 thin films have been prepared by sol-gel dip-coating process from colloidal aqueous suspension. The effect of doping content on the structural, optical and electrical properties is analyzed. Results from infrared optical transmission and reflection have shown that the higher the Sb concentration the lower the transmission intensity and the higher the reflection signal. Absorption intensity increases as well. Results of X-ray reflectometry and electron microscopy have shown that the density of films fired at 400 °C after each dip is higher than that of multi-dipped films prepared with a single annealing. Both the electrical characteristics in the dark and the increase in conductivity as function of illumination through different filters, at 190 K, evidence that the transport properties of these films are dominated by the presence of defects, including the trapping at grain boundary due to excess of oxygen.